Training on Creating a Simple Composter for Producing Liquid Organic Fertilizer from Household Waste - Sinaga, M. Zulham Efendi; Lenny, Sovia; Andriayani; Zuhra, Cut Fatimah; Suharman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Fertilizer is the main needed for farmers to support agricultural products. However, the availability of chemical fertilizers in the market was once scarce due to its limited availability. To avoid dependence on the need for chemical fertilizers is to look for other alternatives as plant fertilizers. One alternative to chemical fertilizers is compost produced from organic waste. Compost fertilizer is available in several forms, namely solid fertilizer and liquid fertilizer. In this community service, training was conducted on making a simple composter to make organic fertilizer. The composter produced in this activity is very easy to do and made by partners because it comes from materials that are easily obtained around partners. The advantage of this composter is that it can produce both solid fertilizer and liquid fertilizer at the same time, but the concern of the service team is a liquid fertilizer because its use is more practical and easier for plants to absorb. During the training process, the partners were very enthusiastic about participating in the activity and asking questions related to composting. In this composter, the waste used is organic waste resulting from household waste which is placed at the top of the composter. Then the composter is closed and allowed to ferment by microorganisms. The results of organic liquid fertilizer can be accommodated at the bottom of the composter and then applied to plants in a ratio of 1:10.